Pengaruh Budaya Organisasi dan Dukungan Organisasi Persepsian terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening (Management Analysis Journal, 2015)
The purpose of this study is to determine the influence of organizational culture and perceived organizational support (POS) toward employees’ performance analyze mediate organizational commitment influence of organizational culture and POS toward employees’ performance. The population is 97 people production employees of PT Braling Wisnu Satriya and 78 samples obtained using the Slovin formula. Methods of data collection using questionnaires, methods of descriptive analysis, multiple regression analysis and path analysis using SPSS for Windows version 16. The concluded of this study are influence organizational culture and perceived organizational support (POS) toward employees’ performance, and organizational commitment is able to mediating the influence of organizational culture and perceived organizational support toward employees' performance.